Modelo de gestión financiera en la Cooperativa Pablo Muñoz Vega oficina matriz de la ciudad de Tulcán. - Villarreal Ramírez, Diana Yamileth (2016)
In the business world, it is important that companies have adequate financi to hereby improve shareholder wealh and contribute to society; th Management Model for Cooperative office Pablo Muñoz Vega Matrix € designed .; in order to contribute to minimizing liquidity risk. This research consists of the initiation of an introduction, where records « carried out previously is, likewise is the scientific problem, objectives, resea and the research also found. Subsequently is the first chapter, which corresponds to the theoretical fram origin and evolution of the research object followed by the variables init: itis independent Financial Management Model and the dependent is liquis allow critical appraisal of warious theoretical positions. In the second chapter the methodological framework 15 proposed, in w types of research, techniques and instrumerts :s detailed; They are allow! information after anal ysis and interpretation to determine the liquidity risi While in tlve third chapter is the proposal, where the constituent elements which is based on the balanced scorecard structured key Subtes Í strategies and performance indicators for each perspective are develop: conclusions and recommendations